Analysis of Aspects of Implementing Room Rehearsal Simulations and Disaster Emergency Handling Command Post Rehearsals at the BNPB Disaster Management Training Center - Bagus Tjahjono (Budapest International Research and Critics University, 2022)
The purpose of this study was to analyze 9 (nine) aspects of organizing table top exercise and command post exercise, namely participants; creating exercise scenarios; exercise stages; elements, roles and functions in exercise; exercise planning products; execute implementation mechanism; movement of table top exercise; movement of command post exercise and evaluation of the implementation of exercise.The study involved 6 (six) Provincial BPBDs who carried out table top exercise and commands post exercise for disaster emergency response. The approach used in this research is a qualitative method. Data collection techniques used are observation, discussion, and documentation with primary and secondary data sources. The results of the study show that 9 (nine) aspects of organizing exercise had been carried out comprehensively in accordance with the rules, methods and procedures so as to indicate that the process of disaster preparedness training through this exercise has been running well at the BNPB PB Training Center.